Joint discrete approximation of analytic functions by Hurwitz zeta-functions - Balčiūnas, Aidas; Garbaliauskienė, Virginija; Lukšienė, Violeta; Macaitienė, Renata; Rimkevičienė, Audronė (Mathematical Modelling and Analysis, 2022)
Let H(D) be the space of analytic functions on the strip . In this paper, it is proved that there exists a closed non-empty set such that every collection of the functions is approximated by discrete shifts , of Hurwitz zeta-functions with arbitrary parameters